(untitled) (Research, Society and Development, 2021)
The present study aims to provide an understanding of the relationship between animal welfare conditions prior to slaughter and meat quality based on a literature review. For this, a literature search was carried out using the following keywords: Welfare, Animal Welfare, Pre-slaughter, Beef, Meat Quality. From the beginning of the 21st century it was possible to observe a growing increase in research on the subject, this is due to the fact that animal welfare is increasingly related to animal stress, metabolism during rigor mortis - responsible for the conversion of muscle tissue into consumable meat, so consequently end consumers are increasingly demanding in this regard. In the post-slaughter period of cattle, meat quality defects may appear, known as PSE (pale, soft, exudative) and DFD (dark, firm, dry), associated with an abnormal pH of the meat. Animal welfare is closely linked from the creation of animals to the pre-slaughter stage of meat. From the study carried out, it is possible to define the need for further research to assess methods of preventing stress during pre-slaughter.